Randomness analysis on blowfish block cipher using ECB and CBC modes - Al-Abiachi, Ashwak M.; Mahmood, Ramlan; Ahmad, Faudziah; S. Mechee, Mohammed (Science Alert, 2013)
Randomness of the output is one of the significant factors in measuring the security of any cryptographic algorithm.Non-random block cipher is vulnerable to any type of attack.This paper presents the National Institute of Standard and Technology (NIST) statistical tests of the Blowfish algorithm to investigate its randomness.Blowfish algorithm with Electronic Codebook (ECB) and Cipher Block Chaining (CBC) modes were conducted for these tests.In addition, comparisons between them were introduced.The analysis showed that Blowfish algorithm with ECB mode was inappropriate with data such as text and image files which have large strings of identical bytes.This inconsistency is due to the majority of the 188 statistical tests of NIST statistical tests failing in all rounds.